Material Inventory Planning Through Continuous Review System and Periodic Review System Methods - Bawono, Digdo; Winarno, Winarno (Universitas Insan Cendekia Mandiri, 2025)
PT Binder Indonesia is a company that operates and focuses on the manufacturing industry. This company is a supplier of pipe supports and suspension equipment used in various types of industries. Some of the products produced by PT Binder Indonesia include HD PUF Cryogenic Pipe Support, Clamp 2-Bolt Pipe Support, and Clamp 3-Bolt Pipe Support, all of which are pipe products. In producing its products, PT Binder Indonesia certainly requires several types of materials used. One of the materials used is Carbon Steel PLA36.00.10MM. In the production process carried out, there was a problem that occurred in the form of a lack of availability of raw materials Carbon Steel PLA36.00.10MM. As a result, the company cannot meet consumer demand because of this. Therefore, the purpose of this study is to plan the supply of raw materials for PT Binder Indonesia, especially for Carbon Steel PLA36.00.10MM material. The method in this study is through the Continuous Review System (P) and Periodic Review System (Q) to plan the company's raw material inventory. The results of the study showed that the calculation using the Q Method obtained a total cost of Rp. 3,948,822,013. The calculation results using the P Method obtained a total cost of Rp. 3,948,901,550. This shows that the Q Method is able to provide a smaller total cost result when compared to the P Method.